Forces and mechanical energy fluctuations during diagonal stride roller skiing; running on wheels? - Kehler, A.; Hajkova, E.; Holmberg, H. C.; Kram, R. (The Journal of Experimental Biology, 2014)
Mechanical energy is conserved during terrestrial locomotion in two ways; the inverted pendulum mechanism for walking and the spring-mass mechanism for running. Here, we investigated if diagonal stride cross-country roller skiing (DIA) utilizes similar mechanisms. Based on previous studies, we hypothesized that running and DIA would share similar patterns of kinetic energy (KE), gravitational potential energy (GPE) and elastic energy fluctuations as if roller skiing is "running on wheels". Experienced skiers (N=9) walked, ran and roller skied with DIA at 1.25m/s and 3 m/s on a level dual-belt treadmill that recorded perpendicular and parallel forces. We calculated the KE and GPE of the COM from the force recordings. As expected, the KE and GPE fluctuated with an out-of-phase pattern during walking and an in-phase pattern during running. Unlike walking, during DIA, the KE and GPE fluctuations were in-phase as they are in running. However, during the glide phase, KE was dissipated as frictional heat and could not be stored elastically in the tendons like in running. Elastic energy storage and return epitomize running and thus we reject our hypothesis. Diagonal stride cross-country skiing is a biomechanically unique movement that only superficially resembles walking or running.